The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1074/jbc.m103451200
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Protein Kinase C in the Regulation of DNA Mismatch Repair Protein Expression and Function

Abstract: The DNA mismatch repair (MMR) proteins are essential for the maintenance of genomic stability of human cells. Compared with hereditary or even sporadic carcinomas, MMR gene mutations are very uncommon in leukemia. However, genetic instability, attested by either loss of heterozygosity or microsatellite instability, has been extensively documented in chronic or acute malignant myeloid disorders. This observation suggests that in leukemia some internal or external signals may interfere with MMR protein expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 53 publications
4
25
0
Order By: Relevance
“…The same group found that hMSH2 and hMSH6 are phosphorylated in vitro and in vivo, and that phosphorylation is required for nuclear translocation and G-T binding. 35,36 Phosphorylation of hMSH2 can be accomplished by PKC-f and protects hMutSa from degradation by the ubiquitin/proteasome pathway. 37 Cadmium, a known carcinogen and an environmental concern from improperly disposed rechargeable batteries, was recently shown to inhibit MMR, leading to an increase in mutation rates up to 2,000-fold.…”
Section: Regulation Of Mmrmentioning
confidence: 99%
“…The same group found that hMSH2 and hMSH6 are phosphorylated in vitro and in vivo, and that phosphorylation is required for nuclear translocation and G-T binding. 35,36 Phosphorylation of hMSH2 can be accomplished by PKC-f and protects hMutSa from degradation by the ubiquitin/proteasome pathway. 37 Cadmium, a known carcinogen and an environmental concern from improperly disposed rechargeable batteries, was recently shown to inhibit MMR, leading to an increase in mutation rates up to 2,000-fold.…”
Section: Regulation Of Mmrmentioning
confidence: 99%
“…The results presented here are representative of three independent experiments. (Humbert et al, 2002). In the same experiment, we also examined the G2/M checkpoint recovery efficiency by monitoring histone-gH2AX labeling in mitotic cells, as it has been shown that the level of its expression correlates with the amount of double-strand breaks (DSBs) in the DNA (McManus and Hendzel, 2005;Bouquet et al, 2006).…”
mentioning
confidence: 99%
“…Ubiquitination and degradation rates of hMSH2 and hMSH6 appear quite similar, suggesting that UPS-mediated proteolysis may maintain a constant ratio of these two proteins (Hernandez-Pigeon et al, 2004). While no strong correlation between total proteasomal activity and the degradation rate of hMutS has been observed in vitro, low hMutS expression in cells is a limiting factor for MMR and indicative of proteolytic activity of the UPS in MMR regulation (Ciechanover, 1994;Humbert et al, 2002;Hernandez-Pigeon et al, 2004). This process is regulated also by an atypical protein kinase C (PKC ); this kinase increases hMutS protein levels and the binding of hMutS to G•T mismatches (Hernandez-Pigeon et al, 2005).…”
Section: Mismatch Repair and The Upsmentioning
confidence: 99%
“…The UPS is involved in post-transcriptional regulation of hMutS protein expression (Humbert et al, 2002;Hernandez-Pigeon et al, 2004). Ubiquitination and degradation rates of hMSH2 and hMSH6 appear quite similar, suggesting that UPS-mediated proteolysis may maintain a constant ratio of these two proteins (Hernandez-Pigeon et al, 2004).…”
Section: Mismatch Repair and The Upsmentioning
confidence: 99%